Migration and diversity in Asian contexts - Lai, Ah Eng; Collins, Francis L.; Yeoh, Brenda S.A (Institute of Southeast Asian Studies, 2013)
This book provides an interesting insight into issues of migration and diversity in Asia, focusing on different scales, and incorporating everyday experiences through in depth analyses of different case studies. In drawing on a range of academic disciplines, and in utilizing numerous methodological approaches, the chapters within the book also demonstrate a breadth and depth of knowledge, thereby contributing not only to migration literature in the region, but migration literature more broadly, subsequently offering a complex negotiation of the different pathways of migration research and beyond. In focusing on migration as both historical legacy and contemporary issue, the chapters within the book bring new light to migration research, demonstrating the inherent importance of looking back in order to look forwards, and drawing together the global and the local through a process of 'glocalization' (Massey, 1991) which is seldom discussed in such detail; the contributions of this book, then, are multiple, and demonstrate a move forward in migration action research that draws together the state, the people, and everyday experience to investigate issues within migration and diversity in light of contemporary globalization and increased interconnectivity in the world today.